2015
DOI: 10.1016/j.bbadis.2014.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin ameliorates testicular damage in diabetic rats by suppressing cellular stress-mediated mitochondria and endoplasmic reticulum-dependent apoptotic death

Abstract: In the present study, we sought to explore whether curcumin plays any beneficial role against STZ induced testicular abnormalities in diabetic rats, and if so, what possible mechanism it utilizes to provide protection. Exposure to STZ (50mg/kg body weight, i.p., once) reduced testis-to-body weight ratio, enhanced blood glucose level and intracellular ROS, altered testicular markers, diminished serum testosterone and impaired cellular redox balance. Administration of curcumin at a dose of 100mg/kg body weight f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
86
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(97 citation statements)
references
References 55 publications
7
86
0
1
Order By: Relevance
“…Calpain may be responsible for cleaving procaspase-12, a caspase localized in ER to generate active caspase-12. Furthermore, caspase-12-deficient cells are resistant to inducers of ER stress, suggesting that caspase-12 is responsible in ER stress-induced apoptosis (Nakagawa and Yuan, 2000;Nakagawa et al, 2000;Rashid and Sil, 2015a;Rashid and Sil, 2015b). Caspase-12 translocates from ER to cytosol and then directly cleaves pro-caspase-9, which, in turn, activates caspase 3 that leads to cell death (Morishima et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Calpain may be responsible for cleaving procaspase-12, a caspase localized in ER to generate active caspase-12. Furthermore, caspase-12-deficient cells are resistant to inducers of ER stress, suggesting that caspase-12 is responsible in ER stress-induced apoptosis (Nakagawa and Yuan, 2000;Nakagawa et al, 2000;Rashid and Sil, 2015a;Rashid and Sil, 2015b). Caspase-12 translocates from ER to cytosol and then directly cleaves pro-caspase-9, which, in turn, activates caspase 3 that leads to cell death (Morishima et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Curcumin is a natural antioxidant, and has efficiency as an anti-apoptotic, cryoprotective, anti-oxidative, anti-inflammatory, anti-toxic and anti-cancer agent (Surh et al 2001;Mathuria and Verma 2008;Glombik et al 2014;Rashid and Sil 2015). Further, many studies in the literature have doi: 10.17221/8677-VETMED concluded that curcumin has potential in the prevention and treatment of a variety of diseases.…”
mentioning
confidence: 99%
“…It has been experimentally shown in different diabetic models that the level of different antioxidants got decreased, both transcriptionally and post-transcriptionally, in kidney tissue [88,89]. It is also shown that prevention of the overproduction of ROS by the administration of exogenous antioxidants is an effective strategy in combating DN [35,90,91]. Numerous studies suggest that antioxidants improve the renal physiology in DN by acting directly against oxidative damage.…”
Section: Antioxidant Therapies In Amelioration Of Diabetic Nephropathymentioning
confidence: 99%
“…Curcumin has caught scientific attention as a potential treatment for DN as it is a commonly consumed natural foodstuff and considered safe compared to the available expensive commercial drugs. Its diverse properties of regulating different signaling pathways, intracellular components and key enzymes are due to its inbuilt antidiabetic, antioxidant and antiinflammatory properties [90,122,123]. Its antioxidant property generally comes up due to its hydroxyl group or the methylene group of the α-diketone (heptadiene-dione) moiety [123].…”
Section: Curcuma Longamentioning
confidence: 99%